Simplifying
2y + 5x + -1z = 4y + 6x
Reorder the terms:
5x + 2y + -1z = 4y + 6x
Reorder the terms:
5x + 2y + -1z = 6x + 4y
Solving
5x + 2y + -1z = 6x + 4y
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
5x + 2y + -6x + -1z = 6x + -6x + 4y
Reorder the terms:
5x + -6x + 2y + -1z = 6x + -6x + 4y
Combine like terms: 5x + -6x = -1x
-1x + 2y + -1z = 6x + -6x + 4y
Combine like terms: 6x + -6x = 0
-1x + 2y + -1z = 0 + 4y
-1x + 2y + -1z = 4y
Add '-2y' to each side of the equation.
-1x + 2y + -2y + -1z = 4y + -2y
Combine like terms: 2y + -2y = 0
-1x + 0 + -1z = 4y + -2y
-1x + -1z = 4y + -2y
Combine like terms: 4y + -2y = 2y
-1x + -1z = 2y
Add 'z' to each side of the equation.
-1x + -1z + z = 2y + z
Combine like terms: -1z + z = 0
-1x + 0 = 2y + z
-1x = 2y + z
Divide each side by '-1'.
x = -2y + -1z
Simplifying
x = -2y + -1z